Preparation method of novel high-performance piezoelectric ceramic material
By adding Sb and Ba elements to the PZT series piezoelectric ceramics and adjusting the process flow, high-performance piezoelectric ceramic materials were prepared, which solved the problem of insufficient performance of existing materials in harsh environments and achieved excellent electromechanical performance. Suitable for a variety of high-performance applications.
Patent Information
- Application Number
- CN202411663904.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing piezoelectric ceramic materials lack sufficient performance in harsh environments such as high temperature and high pressure, making it difficult to meet the modern industry's demand for excellent performance such as high electromechanical coupling coefficient, high voltage electrical coefficient, and high dielectric constant.
Adjust the formulation and process flow by adding Sb and Ba elements to the PZT series piezoelectric ceramics, including batching, mixing, crushing, prefixing, granulation, molding and discharging, sintering, upper electrode, polarization and performance measurements Then, high-performance piezoelectric ceramic materials are prepared.
The piezoelectric constant d33 value is 440pc/N, the electromechanical coupling coefficient kp is 66%, and the relative dielectric constant εrT3 is 1854. The performance is significantly improved. It is suitable for high-resolution, high-sensitivity medical ultrasound imaging and hydroacoustic detection. and high-power density piezoelectric energy collectors and other applications.
Smart Images

Figure CN119462140A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric ceramic materials, and in particular to a method for preparing a novel high-performance piezoelectric ceramic material. Background Art
[0002] Piezoelectric material is a widely used functional material. It can realize the conversion of electrical energy and mechanical energy through the forward and reverse piezoelectric effect. With the development of modern industry, various acoustic transducers and vibration sensors have put forward higher requirements on the performance of piezoelectric materials in harsh environments such as high temperature and high pressure. High-performance piezoelectric materials have excellent properties such as high electromechanical coupling coefficient, high piezoelectric coefficient, and high dielectric constant, which brings hope for the development of broadband, high-resolution, high-sensitivity medical ultrasound imaging and underwater acoustic detection and high-power density piezoelectric energy harvesters. Lead zirconate titanate binary ceramics are a piezoelectric material that has developed rapidly in recent years. It has the characteristics of high dielectric, high voltage, and low loss. It has broad application prospects in micro-displacement drives, ultrasonic transducers, acceleration sensors, etc. Adding elements that are conducive to temperature stability to the PZT series of piezoelectric ceramics to improve their stability has been found to be very effective; therefore, it is necessary to provide a complete method for preparing piezoelectric ceramic materials to achieve the high demand for piezoelectric ceramic performance in current application scenarios. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a method for preparing a new high-performance piezoelectric ceramic material, wherein the preparation method improves the performance of the material by adding Sb and Ba elements to produce a high-performance new piezoelectric ceramic that meets the production requirements, and comprises the following steps:
[0004] Step S1: Mixing ingredients, according to the molecular formula of PbZr 0.52 Ti 0.48 O 3 -x%Sb 2 O 3 +y% aBaO, the value range of xy in the raw material formula is 1 to 3, that is, Sb 2 O 3 , BaO is the mass ratio of the total weight;
[0005] Step S2: Mixing and grinding, using solid phase ball milling method, wherein the weight ratio of ball material to water is 2:1:0.6, and the ball milling time is 20 hours;
[0006] Step S3: Pre-sintering, so that the solid phase chemical reaction of each raw material is fully uniform, a solid solution with a fixed composition is generated, and a main crystal phase is formed. After pre-sintering, crushing is performed to obtain PZT powder. After completion, 100g of PZT powder is weighed and 1%, 2%, and 3% of Sb are added respectively. 2 O 3, and 6g of deionized water was mixed with PZT powder to obtain single Sb doped 3+ The PZT ceramic powders are marked as 1, 2, and 3 respectively;
[0007] Step S4: Granulation, after the synthesized porcelain material is crushed and mixed with a binder (polyvinyl alcohol PVA) accounting for about 5% of the material weight, the mixture is stirred evenly to form particles with good fluidity;
[0008] Step S5: Molding and plastic removal. The molding part is 1t / cm 3 The pre-pressed blocks are crushed and passed through a coarse sieve (50 meshes) to use these coarse particles as dry pressing materials, and then molded into the designed shape using a mold; plastic discharge, before plastic discharge, the binder is first discharged, and then the green body is loaded into a refractory slot plate with good air permeability, pushed into a plastic discharge furnace with good oxygen atmosphere, and plastic discharge is performed according to the heating curve;
[0009] Step S6: sintering, reheating the pre-sintered powder block obtained in step S5 to obtain a piezoelectric ceramic sheet with increased density and enhanced strength;
[0010] Step S7: upper electrode, a conductive electrode is arranged on the surface of the obtained piezoelectric ceramic, and a voltage can be applied to the ceramic piece in the subsequent polarization process; then the ceramic sample is polished, cleaned, dried, and then silver is sintered at 750°C to obtain a silver electrode;
[0011] Step S8: polarization, using a high voltage polarization device to polarize the piezoelectric ceramic at 105° C. for 15 min at 2.2 kV / mm;
[0012] Step S9: Piezoelectric performance measurement, wherein the measurement target is to measure the piezoelectric constant d 33 , electromechanical coupling coefficient kp, relative dielectric constant ε r T 3 , mechanical quality factor Qm, loss tanδ.
[0013] In one embodiment of the present invention, the particle size of the raw material formula in step S1 is not more than 2 μm. The fineness is particularly important for additives with a small amount of addition. The element addition of Sb and Ba adopts Si 2 O 3 and BaCO 3 .
[0014] In one embodiment of the present invention, the volume of the balls in the mixing and crushing step S2 accounts for 30%-40% of the volume of the balls, materials and water. The grinding balls rely on the combined effects of centrifugal force, friction and gravity generated by the motor to form collision, cyclic tumbling and rotation movements, so that the powder in between is subjected to impact and friction grinding, thereby achieving mixing and crushing refinement.
[0015] In one embodiment of the present invention, the relationship between the temperature and the material reaction in the pre-firing step S3 is:
[0016] 500℃~600℃, no reaction;
[0017] 600℃~700℃, PbO+TiO 2 →PbTiO 3 , and at 630℃ Pb 3 TiO 4 Decomposes into PbO;
[0018] 700℃~750℃, PbTiO 3 +PbO+TiO 2 →Pb(Zr 1-x Ti x ) 3 ;
[0019] 750℃~800℃, PbTiO 3 +Pb(Zr 1-x Ti x ) 3 →Pb(Zr 0.5 Ti 0.5 ) 3 .
[0020] In one embodiment of the present invention, the temperature curve for plastic discharge in step S5 is set to heat up to 750°C at a heating rate of 62.5°C / h for 12 hours and then keep warm for 2 hours, during which the furnace door is slightly opened. After the insulation is completed, the power is turned off and the furnace is cooled.
[0021] In one embodiment of the present invention, the sintering temperature in step S6 is 1250° C. and the temperature is maintained for 2 hours.
[0022] The above technical solution of the present invention has the following advantages over the prior art: the preparation method of the piezoelectric ceramic material of the present invention has a simple and sophisticated process, and the piezoelectric constant is controlled at room temperature. 33 The value is 440pc / N, kp=66%, It is 1854; it can be used for high-resolution, high-sensitivity medical ultrasound imaging, underwater acoustic detection, and high-power density piezoelectric energy harvesters, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to make the contents of the present invention more clearly understood, the present invention is further described in detail below based on specific embodiments of the present invention in conjunction with the accompanying drawings.
[0024] Figure 1 It is a process flow chart of the preparation method of the new high-performance piezoelectric ceramic material of the present invention. DETAILED DESCRIPTION
[0025] like Figure 1 As shown, this embodiment provides a method for preparing a new high-performance piezoelectric ceramic material, wherein the preparation method improves the performance of the material by adding Sb and Ba elements to produce a high-performance new piezoelectric ceramic that meets production requirements, and comprises the following steps:
[0026] Mix the ingredients, according to the molecular formula of PbZr 0.52 Ti 0.48 O 3 -x%Sb 2 O 3 +y% aBaO, the value range of xy in the raw material formula is 1 to 3, that is, Sb 2 O 3 , BaO is the mass ratio of the total weight; in order for the chemical reaction of piezoelectric ceramics to proceed smoothly, the raw material particle size is generally required to be no more than 2μm. The fineness is particularly important for additives with a small amount of addition. The element addition of Sb and Ba adopts Si 2 O 3 and BaCO 3 ;
[0027] Mixed grinding: using the traditional solid phase ball milling method, the volume of the ball accounts for 30%-40% of the volume of the ball, material and water, the weight ratio of the ball, material and water is 2:1:0.6, and the ball milling time is 20 hours. The grinding ball is subjected to the combined action of centrifugal force, friction and gravity generated by the motor, forming collision, circular tumbling and self-rotation movements, so that the powder in it is subjected to impact and friction grinding, thereby achieving mixing and crushing refinement.
[0028] Pre-firing: Pre-firing is the process of completing solid-phase chemical reactions and generating porcelain materials through the diffusion of atoms or ions in the raw materials under heating. Pre-firing can make the solid-phase chemical reactions of the raw materials fully uniform, generate a solid solution with a fixed composition, and form a main crystal phase; remove carbon dioxide and moisture in the raw materials, reduce the shrinkage and deformation of the green body during firing, so as to control the external dimensions of the product. Generally, the mixed materials are pressed into blocks and then pre-firing. The purpose is to make the raw materials in close contact, so that the atoms can diffuse more easily and the chemical reaction is more complete.
[0029] Specifically, the relationship between temperature and material reaction during pre-firing:
[0030] 500℃~600℃, no reaction;
[0031] 600℃~700℃, PbO+TiO 2 →PbTiO 3 , and at 630℃ Pb 3 TiO 4 Decomposes into PbO;
[0032] 700℃~750℃, PbTiO 3 +PbO+TiO 2 →Pb(Zr 1-x Ti x ) 3 ;
[0033] 750℃~800℃, PbTiO 3 +Pb(Zr 1-x Ti x ) 3 →Pb(Zr 0.5 Ti 0.5 ) 3 .
[0034] After pre-sintering, the powder was crushed to obtain PZT powder. 1%, 2%, and 3% Sb were added to 100g of PZT powder. 2 O 3 , and 6g of deionized water was mixed with PZT powder to obtain single Sb doped 3+ The PZT ceramic powders are marked as 1, 2, and 3 respectively.
[0035] Granulation: Granulation is to grind the synthesized porcelain material, mix it with a binder (PVA) accounting for about 5% of the material weight, stir it evenly, and make particles with good fluidity. The particles produced by the spray drying granulation method are spherical, have good fluidity, good quality, large output, continuous production, high efficiency, low labor intensity and improved conditions. It is suitable for mass production, but the equipment cost is high.
[0036] Molding and Disassembly:
[0037] Molding is to press the pellets into the required shape and specifications of the green body and create conditions for sintering. There are many ways and methods of green body molding, such as dry pressing molding, plastic molding and slurry molding, etc. Dry pressing molding is currently widely used. 3 The pre-pressed blocks are crushed and passed through a coarse sieve (50 mesh) to use these coarse particles as dry pressing materials. During molding, the granulated granules are loaded into a steel mold of a certain shape. With the help of the mold plug, under the action of external force, the granules are close to each other in the mold, and the internal force firmly connects the granules to form a blank with a certain shape. The effect of dry pressing depends on the pressure of dry pressing, the fluidity of the granules, and the flatness of the mold.
[0038] Plastic removal: The binder in the molded body is a high molecular compound with a high carbon content. When there is insufficient oxygen, carbon burns to produce carbon monoxide with strong reducing properties. Carbon monoxide takes away oxygen from PZT to form carbon dioxide, which reduces metal oxides to conductive metals (such as Pb) and semiconductor low-valent oxides (such as Ti2 O 3 ) affects the color, porcelain formation, silver burning, polarization and final performance of the ceramic. Therefore, the green body must be debinded before sintering.
[0039] The process is to load the green body into a refractory slot plate with good air permeability, push it into a plastic discharge furnace with good oxygen atmosphere, and discharge the plastic according to a certain heating curve. The temperature curve is set to heat up at a heating rate of 62.5℃ / h for 12h to 750℃ and then keep it warm for 2h, during which the furnace door is slightly opened, and the power is turned off after the insulation is completed to cool with the furnace.
[0040] Sintering: Sintering is the phenomenon that the pre-sintered powder block shrinks in volume, increases in density and enhances in strength after being heated to a sufficiently high temperature. The mechanism that realizes the sintering process is the diffusion movement of the atoms (or ions) that make up the substance. The sintering temperature of this experiment is 1250℃, and the temperature is kept for 2h.
[0041] Upper electrode: The upper electrode is a conductive electrode set on the surface of the piezoelectric ceramic, which can apply voltage to the ceramic piece in the subsequent polarization process. The ceramic sample is polished, cleaned, and dried, and then silver is sintered at 750℃ to obtain the silver electrode.
[0042] Polarization: The purpose of polarization is to make the electric domains of piezoelectric ceramics oriented along the direction of the electric field under the action of a strong DC electric field, showing polarity and piezoelectric effect. Polarization conditions: polarization voltage, temperature, time. The polarization voltage (KV) depends on the coercive field EC of the piezoelectric ceramic. It is generally 2-3 times of EC. Generally speaking, the higher the voltage, the more complete the polarization. Under the conditions of a certain polarization electric field and polarization time, the polarization temperature is high, the electric domain orientation is easier to arrange, and it is conducive to polarization. The longer the polarization time, the more complete the electric domain orientation is, and it is conducive to the relaxation of stress during the polarization process.
[0043] In this embodiment, a high voltage polarization device is used to polarize at 2.2 kV / mm for 15 minutes at a temperature of 105°C.
[0044] Measurement of piezoelectric properties: Measurement of the piezoelectric constant d 33 , electromechanical coupling coefficient kp, relative dielectric constant Mechanical quality factor Qm, loss tanδ, etc.
[0045] The experimental results are shown in the following table, i.e. the measurement results of 20x1mm wafer:
[0046]
[0047] It can be seen that Sb 2 O 3 When the mass fraction is 1%, the comprehensive performance is the best. On this basis, BaCO 3 ;
[0048] After pre-sintering, 100 g of powder was crushed and added with 1% Sb 2 O 3 , and 1%, 2%, and 3% BaCO were added respectively. 3 Finally, add about 10 ml of deionized water and mix evenly, and record them as 4, 5, and 6. The measurement results of 20x1mm wafers obtained by the above process are shown in the following table:
[0049]
[0050] The preparation method described in this embodiment, in which the dielectric and piezoelectric properties are comprehensively considered, PZT is doped with 1% Sb 2 O 3 and 2%BaO have the best performance.
[0051] Notes:
[0052] d 33 (piezoelectric constant), tanδ (dielectric loss), kp (electromechanical coupling coefficient), Qm (mechanical quality factor), (Relative dielectric constant).
[0053] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a new high-performance piezoelectric ceramic material, wherein the material properties are improved by adding Sb and Ba elements to produce a new high-performance piezoelectric ceramic that meets production requirements, characterized in that: The steps include: Step S1: Mixing ingredients, according to the molecular formula of PbZr 0.52 Ti 0.48 O3-x%Sb2O3+y%aBaO, the value range of xy in the raw material formula is 1 to 3; Step S2: Mixing and grinding, using solid phase ball milling method, wherein the weight ratio of ball material to water is 2:1:0.6, and the ball milling time is 20 hours; Step S3: pre-sintering to make the solid phase chemical reaction of each raw material fully uniform, generate a solid solution with fixed composition, and form a main crystal phase. After pre-sintering, crushing is performed to obtain PZT powder. Sb2O3 with mass fractions of 1%, 2%, and 3% respectively is added to 100g of PZT powder, and 6g of deionized water is mixed with the PZT powder to obtain single Sb doped 3+ The PZT ceramic powders are marked as 1, 2, and 3 respectively; Step S4: Granulation, crushing the synthesized porcelain material, mixing it with a binder accounting for about 5% of the material weight, and stirring it evenly to form particles with good fluidity; Step S5: Molding and plastic removal. The molding part is 1t / cm 3 The pre-pressed blocks are crushed and passed through a coarse sieve (50 meshes) to use these coarse particles as dry pressing materials, and then molded into the designed shape using a mold; plastic discharge, before plastic discharge, the binder is first discharged, and then the green body is loaded into a refractory slot plate with good air permeability, pushed into a plastic discharge furnace with good oxygen atmosphere, and plastic discharge is performed according to the heating curve; Step S6: sintering, reheating the pre-sintered powder block obtained in step S5 to obtain a piezoelectric ceramic sheet with increased density and enhanced strength; Step S7: upper electrode, a conductive electrode is arranged on the surface of the obtained piezoelectric ceramic, and then the ceramic sample is polished, cleaned, dried, and then silver is sintered at 750°C to obtain a silver electrode; Step S8: polarization, using a high voltage polarization device to polarize the piezoelectric ceramic at 105° C. for 15 min at 2.2 kV / mm; Step S9: Piezoelectric performance measurement, wherein the measurement target is to measure the piezoelectric constant d 33 , electromechanical coupling coefficient kp, relative dielectric constant ε r T 3. Mechanical quality factor Qm, loss tanδ.
2. The method for preparing the piezoelectric ceramic material according to claim 1, characterized in that: The particle size of the raw material formulation in step S1 is no more than 2 μm.
3. The method for preparing the piezoelectric ceramic material according to claim 1, characterized in that: In step S2, the volume of the balls in the mixed crushing accounts for 30%-40% of the volume of the balls, the material and the water.
4. The method for preparing the piezoelectric ceramic material according to claim 1, characterized in that: Relationship between temperature and material reaction in step S3 pre-calcination: 500°C to 600°C, no reaction; 600℃~700℃, PbO+TiO2→PbTiO3, and at 630℃ Pb3TiO4 decomposes into PbO; <h2 style=";text-align:left;direction:ltr">700℃~750℃,PbTiO3+PbO+TiO2→Pb(Zr)<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> )O3; <h2 style=";text-align:left;direction:ltr">750℃~800℃,PbTiO3+Pb(Zr)<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> O3→Pb(Zr)<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> )O3。 5. The method for preparing the piezoelectric ceramic material according to claim 1, characterized in that: In step S5, the temperature curve for plastic discharge is set to heat up at a heating rate of 62.5°C / h for 12h to 750°C and then keep warm for 2h, during which the furnace door is slightly opened. After the insulation is completed, the power is turned off and the furnace is cooled.
6. The method for preparing the piezoelectric ceramic material according to claim 1, characterized in that: In step S6, the sintering temperature is 1250° C. and the temperature is kept for 2 hours.
Citation Information
Patent Citations
Piezoelectric ceramic prepared by adopting antimony-lithium compound substitution for B-site modification of Pb-based lanthanumdoped zirconate titanate and preparation method thereof
CN102557633A
Modified PZT piezoelectric ceramic material and preparation method thereof
CN104129992A
Doped modified lead-based piezoelectric ceramic with excellent and stable piezoelectric property
CN113321507A
Piezoceramic material
GB1401389A
A method for preparing Pb-based peizoelectric ceramicpowder containing the carbonate
KR1020020048102A